1994
DOI: 10.1002/ange.19941061518
|View full text |Cite
|
Sign up to set email alerts
|

Funktionalisierung aromatischer Azoverbindungen durch cobaltkatalysierte, regioselektive Doppeladdition von Tolan: 2,6‐Distilbenylazobenzole und 2,3‐Dihydrocinnoline

Abstract: Die Rontgenstrukt~ranalyse[~~~~ von 3 b ergab, daB zwei Alkinmolekiile in die beiden ortho-C-H-Rindungen eines Benzolringes eingeschoben wurden und eine der so entstandenen transStilbenylgruppen mit der N=N-Bindung zu einem bisher unbekannten 2,3-Dihydrocinnolinring verkniipft wurde (Abb. Das ortho-chinoide System ist durch alternierende C-C-Bindungslangen von etwa 135 und 143 pm und kurze C10-N1-und CIS-C1-Abstande von ca. 132 b m . 137 pm charakterisiert. Das Stickstoffatom N2 liegt nur 1.6 pm iiber der von … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, since we reported that the addition of the ortho C-H bond in aromatic ketones to alkenes can be efficiently attained by the presence of H 2 Ru(CO)(PPh 3 ) 3 as the catalyst, 2 in addition to our finding that the C-H bond cleavage step is not as difficult as had been thought and is not a rate-determining step, 3b a variety of similar C-C bond formations, which involve the cleavage of C-H bonds, have been extended to a wide variety of aromatic and olefinic substrates by a number of research groups. [3][4][5][6][7][8][9][10][11][12][13][14][15] In addition, various functional groups were found to promote the site-selective cleavage of C-H bonds as the directing group.…”
Section: Introductionmentioning
confidence: 99%
“…However, since we reported that the addition of the ortho C-H bond in aromatic ketones to alkenes can be efficiently attained by the presence of H 2 Ru(CO)(PPh 3 ) 3 as the catalyst, 2 in addition to our finding that the C-H bond cleavage step is not as difficult as had been thought and is not a rate-determining step, 3b a variety of similar C-C bond formations, which involve the cleavage of C-H bonds, have been extended to a wide variety of aromatic and olefinic substrates by a number of research groups. [3][4][5][6][7][8][9][10][11][12][13][14][15] In addition, various functional groups were found to promote the site-selective cleavage of C-H bonds as the directing group.…”
Section: Introductionmentioning
confidence: 99%
“…Typical transformations including alkynes are cycloadditions reactions, e.g., Diels-Alder reactions ( Hilt et al, 2006 ) or cyclotrimerization reactions ( Vollhardt, 1984 ), but also Alder-ene-type reactions ( Hilt and Treutwein, 2007 ), whereas the oxidation state of the active species ranges from 0 to + I. Besides, cobalt is also used in C-H activation reactions with either cobalt(0) or cobalt (I) complexes ( Halbritter et al, 1994 ; Gao et al, 2010 ; Fallon et al, 2015 ; Moselage et al, 2015 ) or cobalt(III) complexes as the active species ( Yoshino et al, 2013 ; Zhao et al, 2015 ; Moselage et al, 2016 ).…”
Section: Cobalt-catalyzed Hydroalkynylationmentioning
confidence: 99%